Predictors of Glycaemic control among Adults attending a diabetic Outpatient clinic in a Tertiary hospital, Tanzania: A cross sectional study (Tanzania Medical Journal, 2016)
Background The burden of diabetes mellitus is increasing worldwide and especially so in developing countries. Poor control of diabetes mellitus is associated with the development and progression of many chronic diseases. Proper glycaemic control is important to prevent the development and progression of these complications. In this study, we aimed at assessing the status of glycaemic control and identifying predictors of good glycaemic control among patients with diabetes mellitus type 2 attending an outpatient clinic in Kilombero district, Tanzania.MethodsThis study was a prospective, clinic based, cross-sectional study conducted between August and October 2014 at the St. Francis Referral Hospital diabetic outpatient clinic in Ifakara. A systematic, random sample of 221 patients was enrolled for the study. Socio-demographic and clinical characteristics were collected using a structured questionnaire and a data-collecting tool was used to record the laboratory and clinical measurements. Fasting blood glucose was measured in all patients and the level of ?7.2mmol/dl was considered good glycaemic control. Logistic regression was used to assess association between different variables and glycaemic control.Results Out of the 221 patients involved in the study, 65 (29.4%) had good glycaemic control. Factors associated with good glycaemic control included having received diabetes education (OR [95% CI] = 13.8 [5.95-31.9], p = < 0.001), engaging in regular physical exercise (OR [95% CI] = 5.26 [1.95-14.2], p=0.001), having health insurance (OR [95% CI] = 2.44 [1.08-5.49], P = 0.03) and the use of monotherapy (OR [95% CI] = 7.24 [1.70-30.8], p= 0.007). Duration of diabetes, age and BMI were not associated with glycaemic control in this study.ConclusionThe majority of patients had poor glycaemic control in this population. Health care resource allocation to diabetes and counseling patients to engage in physical activity are important to improve glycaemic control in type 2 diabetic patients.